Physical and nutritional qualities of eggs and meats fed shrimp head meal to layer chicken - Yeasmin, S; Islam, MS; Nath, SD; Islam, SS (Bangladesh Journal of Animal Science, 2021)
The experiment was conducted to investigate the effects of substitution of soybean meal of laying hens ration by shrimp head meal (SHM) on physical and nutritional quality of eggs and meats. Three hundred Hisex White laying hens were divided into five treatment groups and allocated five experimental diets included different levels of SHM. Soybean meal contents of control ration was substituted by SHM meal at the rate of 25, 50, 75 and 100%, respectively. Samples of SHM, eggs and meats were subjected to proximate analysis. Physical properties of eggs and meats were also analyzed following the standard procedures. Highest CP contents (%) of eggs were recorded to be 11.39±0.27 and 10.83±0.18 at initial and peak production periods, respectively in laying hens group fed ration substituted SBM by SHM at the rate of 25%. Significantly (p<0.001) highest value of redness (a*) of egg yolk was recorded to be 1.39 in laying hens group fed diet where SBM was completely substituted by SHM and lowest to be -3.11 in control group (no substitution) at initial production stage (18th to 20th week). Significantly (p=0.05) highest CP (%) contents of meats was found to be 19.37±0.36 in laying hens fed diets substituted SBM at the rate of 75% by SHM and lowest in complete substituted group. It can be concluded that substitution of soybean meal of laying hens ration at the rate of 25% by SHM is suitable for better egg and meat quality. Bang. J. Anim. Sci. 2021. 50 (1):12-21